Rebel Politics : A Political Sociology of Armed Struggle in Myanmar's Borderlands - Brenner, David, 1986- (Book collections on Project MUSE., 2019)
"Drawing on extensive fieldwork on the internal politics of the Kachin and Karen rebel movements, the book analyses the hidden social dynamics and everyday practices of political violence in Myanmar's war-torn borderlands to present a perspective on one of the world's longest running but least researched armed conflicts"--